Antibacterial activity of secondary metabolite compounds from leaf of Eclipta alba L. Hassk - Kartini Hasballah; . Murniana; Nurdin Saidi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Two secondary metabolite compounds of steroid and triterpenoid derivates had been extracted from the leaf of Eclipta alba L. Hassk. The extraction of the compounds was carried out by maceration and then isolated by column chromatography. Structural elucidation was established using GC-MS. Both of the compounds showed antibacterial activity against S. mutans, A. viscosus, and L. kaesal at the concentration of 5%, 10%, and 25%.